Validity and test-retest reliability of the Brazilian version of the Return-to-work self-efficacy questionnaire - João Silvestre Silva-Junior; Ester Paiva Souto; Frida Marina Fischer; Rosane Härter Griep (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To investigate the validity and test-retest reliability of the Brazilian version of the Dutch questionnaire "Verwachtingen over werken". METHODS We analyzed data from a longitudinal study conducted in the city of São Paulo, Brazil, from 2014 to 2016. Participants were 411 workers on sick leave for more than 15 days due to mental disorders. A subsample of 126 participants responded the questionnaire a second time, seven to 21 days later. Factorial and concurrent validities and the test-retest reliability were analyzed. RESULTS Most participants were female (71.5%), the average age was 36.7 years; 83.1% had attended 12 or more years of formal schooling; the average length of sick leave was 84 days. The average self-efficacy score tended to be below the scale midpoint. The construct had a two-dimensional structure and the concurrent validity confirmed the original construct. For all items, the test-retest reliability adjusted for prevalence ranged from good (0.70) to almost perfect (0.83). CONCLUSIONS While the two-dimensional structure diverges from the original, other parameters were adequate. Application of the Return-to-work self-efficacy questionnaire to Brazilian workers might contribute to the planning of return-to-work process. Additional studies are needed to complement the analysis of the use of this instrument in Brazil.